Pemikiran Al-Khawarij dan Al-Murji’ah - R, Rahmawati; Amri, Muh.; Santalia, Indo (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article aims to analyze the history of the emergence of the Al-Khawarij and Al-Murji'ah schools as well as the main ideas of these two schools. This article is a literature review. Then, based on the results of the analysis and reading, it was discovered that the cause of the emergence of the Khawarij sect was due to tribal fanaticism, economic factors and religious enthusiasm. Meanwhile, the Murji'ah aliram appears because it is caused by several theories that have explained it; First, the intention is to unite Muslims. secondly, to overcome the division of the people. third, the feud that occurred between Ali and Muawiyah was caused by arbitration or tahkim. The thoughts or understanding that had been developed by the Khawarij were classified into three categories, namely political, theological and social. Then, the understanding of Murji'ah is implemented in several things, both in the political and theological fields. So in the political field, Murjia'ah's understanding always tries to be neutral which is demonstrated in the form of silence. while in the theological field, it is developed in dealing with problems that then arise related to faith, kufr, major sins or venial sins. The implication of understanding Al-Khawarij and Murji'ah is so that Muslims know the beginning of the emergence and the main ideas and teachings of these two schools.